Secondary surgical management of osteoradionecrosis using three-dimensional isodose curve visualization: a report of three cases. Issue 2 (February 2018) - Kraeima, J.; Steenbakkers, R.J.H.M.; Spijkervet, F.K.L.; Roodenburg, J.L.N.; Witjes, M.J.H.
Abstract: Osteoradionecrosis is defined as bone death secondary to radiotherapy. There is a relationship between the radiation dose received and the occurrence of osteoradionecrosis of the jaws, with the risk increasing above a dose of 60 Gy. In cases of class III mandibular osteoradionecrosis, a segmental resection can be indicated. Current practice is to completely remove the affected bone up to the point where the bone looks healthy and is bleeding. Exact resection planning and the use of guided surgery based on imaging of the bone changes have not been reported so far. This article describes a method whereby the radiotherapy dose information is incorporated into the imaging of the affected bone in order to plan a three-dimensional (3D) virtual guided resection and reconstruction of the mandible in osteoradionecrosis. The method enables 3D visualization of each desired dose field in relation to the 3D model of the affected bone. Two types of application – for resection and reconstruction – are described.